Knowledge works : - Fruin, W. Mark (Oxford University Press, 1997)
This book describes why, for the past twenty-five years, Japanese productivity has been growing more rapidly than productivity in the U.S. Unlike other books on the subject of the Japanese success in manufacturing, it looks at what actually happens in factories. The author brings his experience of working at the Yanagicho Works of the Toshiba Corporation, in Kawasaki City. Like so many Japanese factories, this one is highly productive, efficient, and flexible. While the factory is ordinary looking on the outside, its workers are anything but ordinary as they constantly strive to improve the way they work and the quality of the products they produce. The key to this is the continuous creation and application of knowledge throughout the factory, from workers on the shop floor, to research and development engineers, to top management. Fruin explains how Japanese culture and religion prepare workers for their role in this process of creating and disseminating knowledge.